Regional Intervention of Stroke Care to Increase Thrombolytic Therapy for Acute Ischemic Stroke: The Southeast Texas Experience. Issue 8 (August 2018) - Damani, Rahul H.; Anand, Samyuktha; Asgarisabet, Parisa; Bissell, Catherine; Savitz, Sean; Suarez, Jose I.
Abstract : Background and Purpose—: The aims of this study were to investigate the effect of an intervention to unblind data on r-tPA (recombinant tissue-type plasminogen activator) administration and sharing data with chief executive officers of participating hospitals, on r-tPA administration rates postintervention and on potential healthcare cost savings implemented at 26 Southeast Texas Regional Advisory Council hospitals. Methods—: Retrospective analysis of prospective data on thrombolytic therapy from 26 Southeast Texas Regional Advisory Council hospitals, collected between April 2014 and June 2016. The control (blinded) period (Q2-2014 to Q2-2015) was followed by unblinding (Q3-2015). Results—: Intervention was associated with 21.1% increase in r-tPA administration rates, with 38.5% increase in r-tPA administration with door-to-needle time ⩽60 minutes. An absolute increase in r-tPA administration of 2.1% was seen with an average lifetime cost savings of 3.6 million. Conclusions—: Transparent regional data sharing was associated with improved r-tPA administration and healthcare cost savings. Abstract : Supplemental Digital Content is available in the text.